Auditoría de Gestión y su incidencia en la toma de decisiones en el Hospital General Privado Tungurahua ESMEDICAS S.A., cantón Ambato, provincia de Tungurahua, periodo 2022. - Sánchez Ramos, Luis Ángel (2024)
The present investigation at the Tungurahua Private General Hospital ESMEDICAS S.A. The objective was to evaluate the effectiveness, efficiency and effectiveness in key areas: administrative, clinical and financial. The methodology used included field research, documentary bibliographic research to provide theoretical support based on a review of processes, policies and structures, using Internal Control. The 4 phases of the audit were developed, each with their respective objectives, programs and work papers, the internal control questionnaire was developed and carried out to the employees of the different areas, it shows a high level of confidence with 89% and a low risk level of 11%. The working papers outline crucial areas of improvement to strengthen operational effectiveness and efficiency. The implementation of specific actions, such as the redesign of the organizational chart, development of documented policies and improvements in the quality of services and financial management, contributed significantly to optimizing decision making and overall effectiveness of the institution. In conclusion, the audit highlights the need for corrective actions to strengthen the processes and organizational structure. It is recommended to design a new updated organizational chart and document critical policies, establish a quality review committee in the clinical area, implement protocols for the integrity of medical records and develop strategies to improve financial profitability.